Social Internet of Things - Soro, Alessandro; Brereton, Margot; Roe, Paul (Internet of Things, Technology, Communications and Computing,, 2019)
The aim of this book is to stimulate research on the topic of the Social Internet of Things, and explore how Internet of Things architectures, tools, and services can be conceptualized and developed so as to reveal, amplify and inspire the capacities of people, including the socialization or collaborations that happen through or around smart objects and smart environments. From new ways of negotiating privacy, to the consequences of increased automation, the Internet of Things poses new challenges and opens up new questions that often go beyond the technology itself, and rather focus on how the technology will become embedded in our future communities, families, practices, and environment, and how these will change in turn.